2012
DOI: 10.1002/icd.1763
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Preschool Self‐regulation Assessment for Use in Preschool Classrooms

Abstract: To aid in understanding preschoolers' self‐regulation and refinement of measurement, we examined properties of a field‐based assessment battery of preschooler's self‐regulation, the Preschool Self‐regulation Assessment (PSRA). The PSRA, which includes seven age‐appropriate tasks that tap children's executive control, was administered to 313 preschoolers and then to 261 of these children approximately 3 months later. Teachers reported on children's school readiness (social competence and classroom adjustment) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 63 publications
3
54
0
1
Order By: Relevance
“…They reported that a two-factor model, consisting of hot and cool EC factors, fit better than a one-factor model. Other researchers also have reported that a two-factor model consisting of hot and cool EC factors, or a hierarchical model with hot and cool factors subsumed under a global EC factor, fit better than a one-factor model (e.g., Bassett, Denham, Wyatt, & Warren-Khot, 2012; Brock et al, 2009; Denham, Warren-Khot, Bassett, Wyatt, & Perna, 2012; Kim et al, 2013). In contrast to these studies, however, Allan and Lonigan (2011) did not provide support for distinct hot and cool EC factors in a sample of 234 preschool children.…”
mentioning
confidence: 97%
“…They reported that a two-factor model, consisting of hot and cool EC factors, fit better than a one-factor model. Other researchers also have reported that a two-factor model consisting of hot and cool EC factors, or a hierarchical model with hot and cool factors subsumed under a global EC factor, fit better than a one-factor model (e.g., Bassett, Denham, Wyatt, & Warren-Khot, 2012; Brock et al, 2009; Denham, Warren-Khot, Bassett, Wyatt, & Perna, 2012; Kim et al, 2013). In contrast to these studies, however, Allan and Lonigan (2011) did not provide support for distinct hot and cool EC factors in a sample of 234 preschool children.…”
mentioning
confidence: 97%
“…Bassett, Denham, Wyatt, and Warren-Knot (2012) summarized the commonly accepted definition of self regulation as “a broad construct representing the cognitive, motivational-affective, social and physiological processes that modulate attention, emotion, and behavior to a given situation/stimulus, for the purpose of pursuing a goal” (p. 597). The cognitive skills fundamental to self regulation are referred to as executive functions and encompass the interrelated skills of working memory, inhibitory control, and cognitive flexibility (Bassett, et al, 2012; Blair & Ursache, 2011; Denham, Warren-Khot, Bassett, Wyatt, & Perna, 2012; Diamond, 2006; Garon, Bryson, & Smith, 2008).…”
mentioning
confidence: 99%
“…The cognitive skills fundamental to self regulation are referred to as executive functions and encompass the interrelated skills of working memory, inhibitory control, and cognitive flexibility (Bassett, et al, 2012; Blair & Ursache, 2011; Denham, Warren-Khot, Bassett, Wyatt, & Perna, 2012; Diamond, 2006; Garon, Bryson, & Smith, 2008). Self regulation tasks often require the utilization of more than one executive function skill (Denham, et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that these skills develop with age, showing a significant improvement from the age of 5 to 6 years (e.g., Bassett, Denham, Wyatt, & Warren-Khot, 2012).…”
Section: Emotion Regulation In Childhoodmentioning
confidence: 99%